Photoluminescent properties of Al₂O₃ films containing gold nanoparticles, which are prepared by pulse laser deposition - Kaganovich, E.B.; Kizyak, I.M.; Kudryavtsev, A.A.; Manoilov, E.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
Photoluminescent porous films of aluminum oxide containing gold nanoparticles were prepared using pulse laser deposition from backward flow of particles from erosion torch. Measurements of time-resolved photoluminescence spectra revealed high intense photoluminescent band with the peak close to 2.4 eV and its low-energy shoulder at 1.6 - 1.7 eV, high-energy shoulder at 2.9 eV, with relaxation times up to several microseconds. Studied were the influence of formation conditions and gold concentrations in the target on photoluminescent properties of films. The nature of photoluminescence related with radiative recombination of electrons and holes in Au nanoparticles as well as local centers in Al₂O₃ matrix is discussed.